Effect of Diabetes Self-Management Education (DSME) on Glycosylated Hemoglobin in Patients with Gestational Diabetes Mellitus in the Malingping Inpatient Health Center Work Area in 2022 - Nurleni; Omega DR Tahun (Global Writing Academica Researching and Publishing, 2022)
Maternal Mortality Rate (MMR) is an indicator that describes the welfare of society in a country. One of the causes of maternal death is Gestational Diabetes Mellitus. One method that can be used to determine blood glucose control in people with Diabetes Mellitus is the measurement of Glycosylated Hemoglobin (HbA1c) level. Family-based nursing has a positive impact on Diabetes patients, and can significantly reduce glucose and HbA1c levels and Diabetes Self-Management Education is an important component in the care of Diabetes Mellitus patients which is very necessary in an effort to improve the patient's health status. To determine the Effect of Diabetes Self-Management Education (DSME) on Glycosylated Hemoglobin in Gestational Diabetes Mellitus sufferers in the working area of ​​the Malingping Health Center in 2022. Quasy Experimental with Quantitative approach. A sample of 25 Gestational Diabetes Mellitus patient respondents at the Malingping Health Center. As many as 86% of the 25 respondents had an understanding of the importance of DSME and underwent the components of DSME independently at home. And the value of Sig. (2-tailed) = 0.00, which can be concluded that there is an effect of DSME on HbA1c in patients with Gestational Diabetes Mellitus in the working area of ​​the Malingping Health Center in 2022.